Potencial anti-inflamatório da oleorresina de Copaifera paupera (Herzog) Dwyer - Leguminosae - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2015)
The use of natural products as an alternative therapeutic option is increasingly being stimulated. Among the most widely used, there is the oleoresin of copaíba, for its antiinflammatory and healing effects. As a result, the objective of this study was to evaluate the anti-inflammatory potential of the oleoresin of the species Copaifera paupera. For this, the research was approved by the Ethics Committee on Animal Use (CEUA) of UFOPA, No. 01001/2014, as well as the SISBIO 44380-1. The collection and the chemical characterization of oleoresin of the species C. paupera coming from the Tapajós National Forest was held. For biological assays, Rattus norvegicus individuals were used, males and females, healthy and sedentary. Initially, the assessment of acute oral toxicity was made. The test group was treated with 2000 mg / kg (orally) of oleoresin C. paupera and monitored for 14 days for observation of possible toxic reactions. An evaluation of the enzymes alanine aminotransferase, aspartate aminotransferase and gamma-glutamyl transferase was also performed, and haematological analysis. The trichotomy of the dorsum of the animals for applying the substance to be tested (oleoresin of C. paupera in nature; gel copaiba 10% or phonophoresis) was made in the skin irritation test, forming single application groups and applications for 6 days. The formation of erythema / eschar and edema was observed, graduates from degree 0-4. To test the action of the oleoresin on the inflammatory phase of muscle injury, animals were subjected to blunt trauma divided into groups and treated for 1 to 6 days: Control, which received no treatment; Therapeutic ultrasound group; Gel Group of C. paupera 10%; and phonophoresis group. The gastrocnemius muscle of the animals was extracted and subjected to histological routine, stained with hematoxylin-eosin and examined under an optical microscope. The analysis included the parameters: inflammatory infiltrate, necrosis, fibrosis, edema and cells with central core. For evaluation of antiedematogenic activity, the paw edema test induced by carrageenan was carried out, and two administration forms were used as treatments: topical use (fresh and gel at 10%) and orally (10, 100 and 500 mg / kg). As a result, the oleoresin C. paupera presented the major components: α-copaene (38.55%), β-caryophyllene (20.94%) and β-bisabolene (12.37%). There was no morbidity/mortality in animals or changes in hepatobiliary enzymes or in the blood count. Topical administration did not produce skin irritation after a single application, but after 6 consecutive applications, in natura form generated erythema on the back of animals. During the histological evaluation of muscle tissue, the gel copaiba 10% generated reduction of tissue edema on the 2nd day, and reduction of edema and of the inflammatory infiltrate on day 7 after injury. In antiedematogenic activity test, the oleoresin administered orally inhibited the paw edema within 1st hour with 500 mg/kg and 100 mg/kg, and the 2nd and 3rd with the dose of 500 mg/kg. Its administration by topical use showed no antiedematogenic action. From this it is possible to suggest that the oleoresin of Copaifera paupera besides having low toxicity index, can help reduce the acute inflammatory processes.
Keywords: Copaifera; Inflamação; Edema; Toxicidade